Evaluation of shallow cycling on two types of uncompressed automotive Li(Ni1/3Mn1/3Co1/3)O2-Graphite pouch cells. (August 2020) - Lewerenz, Meinert; Rahe, Christiane; Fuchs, Georg; Endisch, Christian; Sauer, Dirk Uwe
Highlights: Strong differences between compressed and uncompressed cells for shallow cycling For uncompressed pouch cells dV/dQ shape is preserved during cycling Similar aging in calendric tests and for shallow cycling of uncompressed cells Irreversible capacity loss rises with cell voltage For irreversible aging u-shape over SOC is only observed for compressed cells Abstract: For this contribution, two generations of uncompressed pouch cells are investigated in cyclic aging tests. The results are analyzed for the key influence factors by opposing the results of both cell setup strategies with results of compressed cells reported in literature. The cells are evaluated with respect to pulse resistance, anode overhang, dV/dQ-analysis, capacity difference analysis, homogeneity of lithium distribution (HLD) and irreversible capacity losses. It is shown, that uncompressed cells reveal, in contrast to compressed cells, a higher HLD, which is demonstrated in the missing dV/dQ flattening over aging. The trends of peak heights in dV/dQ depend mainly on the graphite voltage and expansion characteristics and are therefore different for both cell generations due to different degrees of utilization of the anode. The trends are comparable to calendric aging test results. The irreversible losses for uncompressed cycled cells increase with cell potential while compressed cells show higher losses to lower and higher SOCs caused by low HLD. Therefore, uncompressed cells have a lower risk of developing lithium plating for inhomogeneous distributed active lithium during accelerated aging tests performing a full charge. Comparing both cell generations, the lifetimes show strong deviations and the largest impact is associated with n/p ratio of the anode to the cathode.